Rickettsia lusitaniae sp. nov. isolated from the soft tick Ornithodoros erraticus (Acarina: Argasidae) - Milhano, N. (2017)
In this study a novel Rickettsia from the spotted fever group, isolated from Ornithodoros erraticus soft ticks collected from pigpens in the south of Portugal, is described. After initial screening revealed Rickettsia-positive ticks, isolation attempts were then performed. Successful isolates were achieved by shell-vial technique using Vero E6 cells at 28°C. Molecular characterization of the isolate was performed based on analysis of five rickettsial genes gltA, ompA, ompB, sca1 and htr with their subsequent concatenation along with other rickettsial species resulting in a clustering of the new isolate with Rickettsia felis and Rickettsia hoogstraalii. The degree of nucleotide sequence similarity with other rickettsiae fulfills the criteria for classification of our isolate as a novel species. The name Rickettsia lusitaniae sp. nov. (=CEVDI PoTiRo) is proposed for this new species found in O. erraticus.